Functional characterization of the active Mutator-like transposable element, Muta1 from the mosquito Aedes aegypti. Issue 1 (December 2017) - Liu, Kun; Wessler, Susan
Abstract Background Mutator -like transposable elements (MULEs) are widespread with members in fungi, plants, and animals. Most of the research on the MULE superfamily has focused on plant MULEs where they were discovered and where some are extremely active and have significant impact on genome structure. The maizeMuDR element has been widely used as a tool for both forward and reverse genetic studies because of its high transposition rate and preference for targeting genic regions. However, despite being widespread, only a few active MULEs have been identified, and only one, the riceOs3378, has demonstrated activity in a non-host organism. Results Here we report the identification of potentially active MULEs in the mosquitoAedes aegypti. We demonstrate that one of these, Muta1, is capable of excision and reinsertion in a yeast transposition assay. Element reinsertion generated either 8 bp or 9 bp target site duplications (TSDs) with no apparent sequence preference. Mutagenesis analysis of donor site TSDs in the yeast assay indicates that their presence is important for precise excision and enhanced transposition. Site directed mutagenesis of the putative DDE catalytic motif and other conserved residues in the transposase protein abolished transposition activity. Conclusions Collectively, our data indicates that theMuta1 transposase ofAe. aegypti can efficiently catalyze both excision and reinsertion reactions in yeast. Mutagenesis analysis reveals that several conserved amino acids, including the DDE triad, play important roles in transposase function. In addition, donor site TSD also impacts the transposition ofMuta1 .